Ceramic tile with golden velvet texture and raw stone duplicating effect and preparation method of ceramic tile
Through the differences in surface tension between digital matte deep ink and dry-grain glaze and new suspension agent, the problem of insufficient fine texture and poor anti-fouling performance of ceramic tiles is solved, and the fine concave and convex texture and excellent physical properties of ceramic tiles are achieved, which is close to nature. Marble texture and effect.
Patent Information
- Application Number
- CN202411211498.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-30
AI Technical Summary
When replicating the natural marble texture of existing ceramic tiles, the concave and convex texture is not fine enough. Conventional suspension agents lead to poor anti-fouling performance on the glaze, and digital matte deep ink is difficult to form sufficient repulsion with the dry-grain glaze, which limits the delicateness of the product. and scope of application.
Using digital matte deep ink and developed dry-grain glaze, physical mutual repulsion is formed through surface tension difference, combined with high-temperature deformation and multivalent divalent oxides, ceramic tiles with matte gloss and transparency are prepared, and new suspension agents are used to increase The polarity and surface tension of the suspension agent ensure effective discharge of dry-grain glaze and ink.
The fine concave and convex texture effect of ceramic tiles is achieved, the transparency and wear resistance, acid and alkali resistance and anti-fouling properties of the glaze are improved, making the product closer to the texture and effect of natural marble, and expanding the scope of application.
Smart Images

Figure CN119143390A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a ceramic tile with a velvet texture and a replica of an original stone effect and a preparation method thereof. Background Art
[0002] The development of ceramic tiles is mainly based on natural stone. With the upgrading of inkjet technology, the clarity and texture of patterns are getting closer and closer to the texture of natural stone. With the development of new ceramic materials, the upgrading of glazes, dry granular glazes and production processes, the production technology of ceramic wall and floor tiles has been greatly improved. Not only is the pattern layering effect comparable to that of natural marble, but it is also more excellent than natural marble in terms of performance. The wear resistance, acid and alkali resistance and anti-fouling performance are far superior to natural stone. Ceramic tiles have basically achieved the goal of being derived from natural stone and being better than natural stone.
[0003] The reproduction of natural marble is a major research direction in ceramic production. At present, the texture level has been made very realistic. With the demand of consumers for product effects and R&D personnel for the ultimate product, the concave and convex texture effect naturally formed by matte natural marble is reproduced on ceramic tiles to make the product more three-dimensional. At present, the concave effect is mainly formed by the reaction of sinking ink with the surface glaze, and this type is mainly based on bright marble products. With the rise of matte products, ceramic products with natural concave and convex textures of stone are also the main research and development direction. With the development of production technology and materials, digital molds and glue positioning products have made great progress in simulating natural marble products. Digital mold products use the stacking of digital and glaze to form a more three-dimensional concave texture. Glue positioning uses the method of printing glue patterns with dry particles by inkjet to achieve the product's concave and convex effect.
[0004] At present, the ceramic tiles produced with marble products as materials mainly include bright surface type, which is combined with the concave and convex texture formed by sinking ink. This is the early marble product. The marble formed by this type of product is formed by the reaction of sinking ink with glaze to form shrinkage and cause depression. The depression of this type of product is not fine enough, the texture is coarse, and it is not realistic enough. Digital mold products use the form of digital arrangement of bottom glaze to produce concave and convex texture, but this type is too rough and the concave and convex are deep, which can easily cause problems such as dirt hidden in the gap. The glue positioning type marble products formed by inkjet printing glue can achieve a deep and large concave and convex texture. This process is suitable for marble products with relatively rough textures. At present, the more delicate marble texture requires fine processing of the file, and the fine concave and convex texture effect is formed by arranging the surface glaze. After fine polishing of the surface, it forms a delicate and smooth texture with natural marble after years of use. At present, the surface glaze needs to use ordinary raw glaze and digital matte deep ink to form fine textures. However, ordinary protective glaze has many pores in the glaze layer after firing, which destroys the surface structure after fine polishing, resulting in poor anti-fouling performance of the glaze. With the development of dry granular glaze, dry granular glaze has good anti-fouling performance and wear resistance after being applied to the product again due to its dense structure. However, at present, dry granular glaze needs to be suspended by suspending agent to form glaze slurry. Conventional suspending agents have greater hydrophobicity. When dry granular glaze containing suspending agent and greater hydrophobicity meets digital matte deep ink, it is difficult for digital matte deep ink to form sufficient repulsive force on dry granular glaze, that is, it is difficult to form fine concave and convex textures, which limits the development of such products.
[0005] Therefore, it is necessary to develop a relatively simple production process, which can replicate the surface effect of natural marble through fine texture processing, and form the desired surface texture effect after combining with glaze. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a ceramic tile with a velvet texture and a replica of the original stone effect and a preparation method thereof, using the matte inorganic glaze in the developed digital matte engraving ink, which has a relatively matte texture effect formed after reacting with the surface dry granular glaze, achieving a replica effect that is relatively close to the surface of natural marble; using the developed dry granular glaze, it has a higher transparency and a smaller high-temperature deformation degree, ensuring that the fine concave and convex texture remains relatively intact after firing, and the glaze surface has better physical properties, ensuring a wide range of applications of the product; using the development of the suspending agent in the dry granular glaze, it can be dissolved in water at a larger ratio, avoiding the problem that the conventional suspending agent needs to use ethylene glycol with greater hydrophobicity as a solvent, and the inorganic suspending agent provided by the present invention contains more electrolyte Na +Ions make the dry granular glaze have greater polarity, which can form a greater repulsive force with the digital matte deep ink, thus producing a fine and three-dimensional concave and convex texture effect.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A ceramic tile with a velvet texture and a replica stone effect, comprising a body layer, a glaze layer, a pattern texture layer, a digital engraving ink layer, and a dry granular glaze layer arranged in sequence from bottom to top; the digital engraving ink layer is composed of digital matte engraving ink; the dry granular glaze layer is composed of dry granular glaze; a surface tension difference is formed between the digital matte engraving ink and the dry granular glaze; the surface tension of the digital matte engraving ink is 1.25×10 -2 N / m~2.27×10 -2 N / m, the surface tension of the dry granular glaze is 6.50×10 -2 N / m~6.80×10 -2 N / m. When the subsequently applied dry granular glaze is combined with the digital matte engraving ink, since the digital matte engraving ink has a smaller surface tension and the dry granular glaze has a larger surface tension, the two will physically repel each other when they meet, thus forming a fine concave and convex texture on the digital matte engraving ink.
[0009] Preferably, the digital matte engraving ink comprises 60-65 parts of organic solvent and 35-40 parts of matte inorganic glaze by weight; the organic solvent comprises the following components: 40%-55% isooctyl laurate, 40%-55% ethyl acetate, 3%-6% dispersant, 0.1%-0.2% suspending agent, 0.2%-0.3% defoamer, 0.3%-0.6% leveling agent, and 0.15%-0.3% pH regulator; the chemical composition of the matte inorganic glaze is: Al 2 O 3 :18.45%~21.54%,SiO 2 :45.68%~50.24%, K 2 O: 1.24%~3.25%, Na 2O: 1.25% to 2.58%, CaO: 4.37% to 6.58%, ZnO: 3.24% to 5.58%, BaO: 8.57% to 10.24%, SrO: 6.35% to 8.54%, and the rest are trace impurities and are reduced as appropriate. To prepare a more suitable digital matte deep-cut ink, since the dry granular glaze needs to be spread out to form a fine texture in the present invention, and the dry granular glaze is more difficult to spread out due to the use of a suspending agent compared to conventional glazes, the present invention needs to prepare a digital matte deep-cut ink with greater hydrophobicity, and in order to ensure that the present invention has the luster of natural marble, the part of the digital matte deep-cut ink in contact with the dry granular glaze needs to have a matte luster after firing. The use of organic solvents in the digital matte deep-cut ink of the present invention makes the ink have a lower surface tension and a greater hydrophobic property, so that it has sufficient repulsive force when combined with the dry granular glaze with a larger surface tension and hydrophilicity, so that the dry granular glaze can repel each other with the printed digital matte deep-cut ink and form a fine texture and concave-convex effect. The other main components of digital matte engraving ink are matte inorganic glaze, Al 2 O 3 The application of Al 2 O 3 Can react with SiO in dry granular glaze 2 The reaction forms a mullite crystal phase, which can avoid the formation of too much glass phase and increase the glossiness of the glaze. In addition, the use of polyvalent divalent oxides CaO, ZnO, BaO, and SrO, on the one hand, plays a role of high-temperature fluxing, and on the other hand, helps to extinct. Therefore, the product prepared by the present invention can form a fine, undulating texture, and at the same time can be consistent with the natural gloss of natural marble, so that this product can perfectly replicate the effect of natural marble.
[0010] Preferably, the dry granule glaze comprises 30-40 parts of dry granules and 60-70 parts of suspending agent by weight; the chemical composition of the dry granules is: Al 2 O 3 :16.21%~20.14%,SiO 2 :58.12%~63.34%, B 2 O 3 :4.27%~7.54%, K 2 O: 1.34%~2.34%, Na 2O: 1.56% to 2.54%, CaO: 2.14% to 4.57%, BaO: 2.10% to 5.65%, SrO: 1.87% to 3.98%, and the rest are trace impurities and are reduced as appropriate; preferably, the raw materials of the dry particles are: calcined kaolin: 18 to 22 parts, potassium feldspar: 15 to 25 parts, sodium feldspar: 18 to 28 parts, waste glass: 5 to 8 parts, corundum: 3 to 6 parts, sodium borate: 8 to 12 parts, fluorite: 3 to 7 parts, barium carbonate: 3 to 7 parts, and strontium sulfate: 4 to 8 parts; the raw materials constituting the dry particles are calcined and melted to form a frit, and then the frit is ground and the suspending agent is added to form the dry particle glaze with a particle size range of 80 to 120 μm, so that the dry particle glaze has a suitable particle size and is not easy to settle, so that the powdered dry particles are evenly dispersed in the suspending agent under the action of the suspending agent. Under the premise of replicating natural marble, the present invention also needs to ensure that the dry granular glaze on the pattern texture layer and the digital deep ink layer has good transparency to ensure the clarity of the printed pattern detail texture. Therefore, the dry granular glaze needs to have good high-temperature viscosity so that the fine concave-convex effect formed after firing will not melt and collapse. In addition, the dry granular glaze layer is also required to have compactness, a mature state after firing, acid and alkali resistance, and excellent anti-fouling performance, so as to achieve multi-regional application of ceramic wall and floor tiles. Specifically, the calcined kaolin in the dry granules is mainly used to provide aluminum oxide and silicon dioxide, which can be used to improve the high-temperature viscosity of the dry granules, ensure that the glaze surface does not collapse after firing and forming in the product, and has a three-dimensional texture effect. The application of waste glass is mainly used to provide sufficient silicon dioxide, so that the dry granular glaze is easier to form a glass phase after firing, thereby increasing the transparency of the dry granular glaze layer. The main component of fluorite is calcium fluoride. When making dry-grain glaze, due to the decomposition characteristics of calcium fluoride, the dry particles can react more fully during firing. At the same time, the CaO provided, as well as the divalent oxides such as BaO and SrO provided by barium carbonate and strontium sulfate, can make the dry-grain glaze layer have a matte luster after firing, achieving the replica effect of natural marble.
[0011] Preferably, the suspending agent comprises the following components: sodium methylcellulose: 1.5-3.5 parts, sodium polyacrylate: 5-10 parts, sodium alginate: 3-8 parts, water-soluble biopolysaccharide: 5-10 parts, water: 70-85 parts. One of the inventive points of the present invention is the research and development of the suspending agent in the dry particle glaze. Conventional suspending agents have greater hydrophobicity, and the dry particles have a greater mass. When the dry particle glaze with greater hydrophobicity meets the digital matte deep ink, the digital matte deep ink is difficult to form a sufficiently large repulsive force on the dry particle glaze, resulting in an insufficiently fine effect of the expulsion. Compared with the conventional suspending agent currently formed by mainly using sodium methylcellulose and dissolving it with ethylene glycol, the suspending agent provided by the present invention has greater hydrophobicity. When the conventional suspending agent is combined with the digital matte deep ink with greater hydrophobicity, it is difficult to form a mutually repulsive effect between the two, that is, it is difficult to form a relatively fine, three-dimensional concave and convex texture. The suspension prepared by the present invention mainly uses sodium methylcellulose combined with sodium polyacrylate, sodium alginate and water-soluble biopolysaccharides. Sodium polyacrylate has strong viscosity and suspension, has a large solubility in water, and forms a highly active Na + Sodium alginate has a large solubility in water. After dissolving, it can increase the suspending properties of the suspending agent. At the same time, the electrolyte Na + , which can increase the fluidity of the suspension, making it easier to implement the spraying process of the dry granular glaze. The water-soluble biopolysaccharide improves the viscosity of the suspension after dissolving in water. Its strong intermolecular bond force can make the granular dry particles form a more compact and evenly dispersed dry granular glaze. The use of this composition increases the Na + The content of suspending agent makes the suspending agent have strong hydrophobicity and large surface tension. When the dry granular glaze containing suspending agent with large polarity and large surface tension meets the digital matte deep-engraving ink with small surface tension and large hydrophobicity, the repulsive force between the two makes the dry granular glaze tightly adhered to the suspending agent be pushed away together, thus forming a finer and bumpy glaze effect. The present invention can form fine textures with the finest range of 0.01-0.05mm on the brick surface, and can also form block-shaped bumpy textures with a larger area, and can form block-shaped bumpy textures with a maximum area of 8-10 square centimeters. The multi-dimensional three-dimensional bumps and depressions combined with points, lines and surfaces make the product have a more realistic replica effect of natural marble.
[0012] Another object of the present invention is to provide a method for preparing a ceramic tile having a velvet texture and a replica of an original stone, comprising the following steps:
[0013] S1, pressing the powder to form a green body layer;
[0014] S2, applying a glaze on the body layer to form a glaze layer;
[0015] S3. First, print the color texture on the surface glaze layer to form the pattern texture layer. The color pattern mainly selects the pattern material with natural marble effect; then print the digital matte deep-engraving ink on the pattern texture layer to form a digital deep-engraving ink layer; the digital matte deep-engraving ink forms different grayscale value textures through the texture setting. When the subsequent digital matte deep-engraving ink is combined with the dry granular glaze, since the digital matte deep-engraving ink has greater hydrophobicity and smaller surface tension, and the dry granular glaze has greater polarity and greater surface tension, the two will form physical mutual repulsion after meeting, so that different depths and shapes of concave and convex textures can be formed according to different printed digital grayscales, that is, fine concave and convex textures are formed on the fired brick surface.
[0016] S4, applying dry granular glaze on the formed digital engraving ink layer to form a dry granular glaze layer; preferably, the dry granular glaze is applied by spraying. When the dry granular glaze encounters the digital matte engraving ink under the dispersion effect of the suspending agent, due to the large surface tension difference between the two, the dry granular glaze is arranged according to the different inkjet amounts of the digital matte engraving ink, and after being arranged according to the different pixels and depths of the design file, a concave and convex texture of different depths and shapes can be formed.
[0017] S5. The green body layer coated with the dry granular glaze is fired and formed to obtain the ceramic tile having the texture of golden velvet and the effect of replicating the original stone.
[0018] Preferably, the powder in step S1 is pressed into a brick of the desired thickness and size by a brick press, and then dried. After drying, the moisture content of the brick is controlled below 0.5%, and the strength of the brick is controlled above 1.8 MPa. The above limitation can ensure that the brick has a certain strength, which is convenient for the subsequent glazing process.
[0019] Preferably, the chemical composition of the glaze in step S2 is: Al 2 O 3 :23.24%~25.67%,SiO 2 :51.24%~53.65%, ZrO 2 :6.32%~8.58%, K 2 O: 2.45%~3.68%, Na 2 O: 1.67% ~ 2.69%, CaO: 1.17% ~ 2.56%, MgO: 2.30% ~ 3.65%, Fe 2 O 3 :0.56%~0.89%,TiO 2 :0.35%~0.68%, the rest is reduced as appropriate. The above glaze has high high temperature viscosity and hiding power.
[0020] More preferably, the specific gravity of the glaze is 1.85-1.90 g / ml, and the glaze application amount is 300-400 g / m 2 .
[0021] Preferably, the firing temperature of the firing molding in step S5 is 1180-1190°C, and the firing time is 60-65 minutes. The above firing temperature is compatible with the melting temperature of the digital matte engraving ink and the dry granular glaze, and can form a fine, concave and convex texture effect on the brick surface without the concave and convex texture being filled due to melting due to the firing temperature being too high.
[0022] Beneficial effects:
[0023] The present invention provides a ceramic tile with a velvet texture and a replica of an original stone effect and a preparation method thereof, which has the following advantages:
[0024] 1. For conventional dry granule glaze products, it is often difficult to show a delicate and three-dimensional concave-convex texture effect when using digital matte deep-engraving ink. The present invention uses the developed suspending agent, which can, on the one hand, make the powdered dry particles more evenly dispersed in the suspending agent, and on the other hand, this new suspending agent has a large polarity. When encountering the digital matte deep-engraving ink with strong hydrophobicity, it can form a large repulsive force between each other according to the pre-printed texture. Moreover, this suspending agent can produce a strong bonding ability with the dry granule particles, so that the dry granule glaze can follow the repulsive force of the two to form a more delicate and three-dimensional concave-convex effect.
[0025] 2. The matte marble products prepared with the developed dry granular glaze as the surface glaze have better physical properties than conventional water glaze, which is mainly reflected in the better transparency of the glaze layer, clearer patterns and more prominent texture details; at the same time, the glaze layer also has better wear resistance, acid and alkali resistance and anti-fouling properties, giving ceramic tiles a wider application space.
[0026] 3. Research and development of digital matt engraving ink. Compared with conventional sinking ink and carving ink, the digital matt engraving ink of the present invention can react with the dry particle glaze in the present invention during the firing process to form a matt luster and a relatively three-dimensional non-collapse effect through the research and development of matt inorganic glaze in the digital matt engraving ink and the adjustment of the formula; in addition, the digital matt engraving ink can react with the oxides in the dry particle glaze during the firing process to form a variety of crystals with different reflectivities, forming a matt luster, which can perfectly replicate the effect of natural marble in terms of visual effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the ceramic tile with velvet texture and replica of original stone effect prepared in Example 1.
[0028] Figure 2This is an optical microscope magnified image of the ceramic tile with a velvet texture and a replica of the original stone effect obtained in Example 1.
[0029] Figure 3 This is a schematic diagram of a ceramic tile having a velvet texture and a replica of an original stone effect obtained in Example 2.
[0030] Figure 4 This is a schematic diagram of the ceramic tile prepared in Comparative Example 2. DETAILED DESCRIPTION
[0031] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0032] Example 1
[0033] A ceramic tile with a velvet texture and a replica of an original stone effect comprises a body layer, a surface glaze layer, a pattern texture layer, a digital engraving ink layer, and a dry granular glaze layer which are arranged in sequence from bottom to top; the digital engraving ink layer is composed of digital matte engraving ink; the dry granular glaze layer is composed of dry granular glaze; a surface tension difference is formed between the digital matte engraving ink and the dry granular glaze.
[0034] Calculated by weight, the digital matt engraving ink includes 62 parts of organic solvent and 38 parts of matt inorganic glaze; the organic solvent includes the following components: 47.5% isooctyl laurate, 47% ethyl acetate, 4.5% dispersant, 0.2% suspending agent, 0.2% defoamer, 0.4% leveling agent, and 0.2% pH value regulator; the chemical composition of the matt inorganic glaze is: Al 2 O 3 : 19.99%, SiO 2 : 47.96%, K 2 O: 2.24%, Na 2 O: 1.91%, CaO: 5.47%, ZnO: 4.41%, BaO: 9.40%, SrO: 7.44%, the rest are trace impurities and reduced as appropriate;
[0035] Calculated by weight, the dry granule glaze includes 35 parts of dry granules and 65 parts of suspending agent; the raw materials of the dry granules are: calcined kaolin: 20 parts, potassium feldspar: 20 parts, sodium feldspar: 23 parts, waste glass: 6.5 parts, corundum: 4.5 parts, sodium borate: 10 parts, fluorite: 5 parts, barium carbonate: 5 parts, strontium sulfate: 6 parts; the chemical composition of the dry granules is: Al2 O 3 : 18.17%, SiO 2 : 60.73%, B 2 O 3 :
[0036] 5.90%, K 2 O: 1.84%, Na 2 O: 2.05%, CaO: 3.35%, BaO: 3.87%, SrO:
[0037] 2.92%, the rest are trace impurities and reduced as appropriate; the suspending agent includes the following components: sodium methylcellulose: 2 parts, sodium polyacrylate: 7.5 parts, sodium alginate: 5.5 parts, water-soluble biopolysaccharide: 7.5 parts, water: 77.5 parts. The particle size of the dry granular glaze is 80-90 μm.
[0038] The chemical composition of the glaze in the glaze layer is: Al 2 O 3 : 24.67%, SiO 2 : 51.65%, ZrO 2 : 7.34%, K 2 O: 3.48%, Na 2 O: 1.88%, CaO: 1.86%, MgO: 3.05%, Fe 2 O 3 : 0.59%, TiO 2 :0.45%, the rest is reduced. The specific gravity of the glaze is 1.85g / ml, and the glaze amount is 320g / m 2 .
[0039] The firing temperature of the ceramic tile is 1180-1190° C., and the firing time is 60-65 minutes.
[0040] Example 2
[0041] Compared with Example 1, Example 2 is different in that:
[0042] 1. The content of aluminum oxide in the dry granular glaze is 16.25%. The chemical composition of the dry granules is as follows: Al 2 O 3 : 16.25%, SiO 2 : 61.93%, B 2 O 3 : 5.95%, K 2 O: 1.93%, Na 2 O: 2.15%, CaO:
[0043] 3.24%, BaO: 3.90%, SrO: 2.87%, and the rest are trace impurities and reduced as appropriate. The particle size of the dry granular glaze is 100-110 μm. It is used to examine the effect of low aluminum content in the dry granular glaze on the glossiness of the glaze surface and the effect on the three-dimensional effect of the glaze surface.
[0044] 2. The chemical composition of the glaze in the glaze layer is: Al 2 O 3 : 25.24%, SiO 2 : 52.42%, ZrO 2 : 6.85%, K 2 O: 2.86%, Na 2 O: 2.43%, CaO: 2.03%, MgO: 2.75%, Fe 2 O 3 : 0.74%, TiO 2 :0.56%, the rest is reduced. The specific gravity of the glaze is 1.89g / ml, and the glaze amount is 380g / m 2 .
[0045] Example 3
[0046] The difference between Example 3 and Example 1 is that the content of aluminum oxide in the dry granular glaze is 20.10%, and the chemical composition of the dry granules is specifically: Al 2 O 3 :20.10%,SiO 2 : 58.43%, B 2 O 3 : 5.93%, K 2 O: 1.94%, Na 2 O: 2.08%, CaO: 3.29%, BaO: 3.88%, SrO: 3.57%, the rest are trace impurities and are reduced as appropriate. It is used to examine the effect of high aluminum content in dry particles on the glossiness of the glaze and the effect on the three-dimensional effect of the glaze.
[0047] Example 4
[0048] Compared with Example 1, Example 4 is different in that the content of waste glass in the dry granular raw material is 5 parts, and the chemical composition of the dry granules is specifically: Al 2 O 3 :19.30%,SiO 2 : 58.13%, B 2 O 3 : 5.69%, K 2 O: 1.93%, Na 2O: 2.38%, CaO: 2.99%, BaO: 3.78%, SrO: 3.58%, the rest are trace impurities and reduced accordingly. Used to examine the effect of the transparency of dry granular glaze on the clarity of the pattern.
[0049] Example 5
[0050] Compared with Example 1, Example 5 is different in that the content of waste glass in the dry granular raw material is 8 parts, and the chemical composition of the dry granules is specifically: Al 2 O 3 : 19.31%, SiO 2 : 63.33%, B 2 O 3 : 4.99%, K 2 O: 1.95%, Na 2 O: 2.48%, CaO: 3.69%, BaO: 3.78%, SrO: 2.18%, the rest are trace impurities and reduced accordingly. Used to examine the effect of the transparency of dry granular glaze on the clarity of the pattern and the three-dimensional effect of the glaze.
[0051] Example 6
[0052] Compared with Example 1, Example 6 is different in that the contents of BaO and SrO in the dry granule glaze are both lower limits, and the chemical composition of the dry granules is specifically: Al 2 O 3 : 19.43%, SiO 2 : 60.33%, B 2 O 3 : 4.29%, K 2 O: 1.55%, Na 2 O: 2.39%, CaO: 3.79%, BaO: 2.10%, SrO: 1.87%, the rest are trace impurities and are reduced as appropriate. Used to examine the effects of divalent oxides on glaze gloss and three-dimensional effect.
[0053] Example 7
[0054] Compared with Example 1, Example 7 is different in that the contents of BaO and SrO in the dry granule glaze are both upper limits, and the chemical composition of the dry granules is specifically: Al 2 O 3 : 19.43%, SiO 2 : 60.33%, B 2 O 3 : 4.29%, K 2 O: 1.55%, Na 2O: 2.28%, CaO: 3.79%, BaO: 5.65%, SrO: 3.98%, the rest are trace impurities and are reduced as appropriate. Used to examine the effects of divalent oxides on glaze gloss and three-dimensional effect.
[0055] Example 8
[0056] The difference between Example 8 and Example 1 is that the Al content in the matte inorganic glaze in the digital matte engraving ink is 2 O 3 The content of is the lower limit, and its specific chemical composition is: Al 2 O 3 : 18.45%, SiO 2 : 50.16%, K 2 O: 2.11%, Na 2 O: 1.27%, CaO: 4.45%, ZnO: 5.42%, BaO: 9.38%, SrO: 7.22%, the rest are trace impurities and are reduced as appropriate. Used to examine the influence of digital matte engraving ink on the brightness of the glaze concave and convex effect position and three-dimensional effect.
[0057] Example 9
[0058] The difference between Example 9 and Example 1 is that the Al content in the matte inorganic glaze in the digital matte engraving ink is 2 O 3 The content of is the upper limit, and its specific chemical composition is: Al 2 O 3 : 21.54%, SiO 2 : 45.96%, K 2 O: 2.21%, Na 2 O: 1.87%, CaO: 4.47%, ZnO: 5.40%, BaO: 9.36%, SrO: 7.31%, the rest are trace impurities and are reduced as appropriate. Used to examine the influence of digital matte engraving ink on the brightness of the glaze surface concave and convex effect position and three-dimensional effect.
[0059] Example 10
[0060] Compared with Example 1, Example 10 is different in that the contents of divalent oxides ZnO, BaO, and SrO in the matte inorganic glaze in the digital matte engraving ink are all lower limits, and the specific chemical composition is: Al 2 O 3 : 19.54%, SiO 2 : 48.96%, K 2 O: 2.12%, Na 2O: 1.99%, CaO: 5.77%, ZnO: 3.24%, BaO: 8.58%, SrO: 6.39%, the rest are trace impurities and can be reduced as appropriate. Used to examine the effect of the lower limit of the divalent oxide content on the brightness and three-dimensional effect of the glaze surface concave and convex effect position.
[0061] Embodiment 11
[0062] Compared with Example 1, Example 11 is different in that the contents of divalent oxides ZnO, BaO, and SrO in the matte inorganic glaze in the digital matte engraving ink are all upper limits, and the specific chemical composition is: Al 2 O 3 : 21.54%, SiO 2 : 45.96%, K 2 O: 2.21%, Na 2 O: 1.87%, CaO: 4.47%, ZnO: 5.58%, BaO: 10.24%, SrO: 8.54%, the rest are trace impurities and can be reduced as appropriate. Used to examine the influence of the divalent oxide content on the brightness and three-dimensional effect of the glaze surface concave and convex effect when it is at the upper limit.
[0063] Example 12
[0064] The difference between Example 12 and Example 1 is that the composition of the suspending agent in the dry granular glaze is different, that is, the content of sodium polyacrylate in the suspending agent of Example 12 is the lower limit: 5 parts. It is used to examine the suspension effect of the dry granular glaze and the concave-convex effect of the glaze surface.
[0065] Embodiment 13
[0066] Compared with Example 1, Example 13 is different in that the composition of the suspending agent in the dry granular glaze is different, that is, the content of sodium polyacrylate in the suspending agent of Example 13 is the upper limit: 10 parts. It is used to examine the suspension effect of the dry granular glaze and the concave-convex effect of the glaze surface.
[0067] Embodiment 14
[0068] Compared with Example 1, Example 14 is different in that the composition of the suspending agent in the dry granular glaze is different, that is, the content of sodium alginate in the suspending agent of Example 14 is the lower limit: 3 parts. It is used to examine the suspension effect of the dry granular glaze and the concave-convex effect of the glaze surface.
[0069] Embodiment 15
[0070] Compared with Example 1, Example 15 is different in that the components of the suspending agent in the dry granular glaze are different, that is, the content of sodium alginate in the suspending agent of Example 15 is the upper limit: 8 parts. It is used to examine the suspension effect of the dry granular glaze and the concave-convex effect of the glaze surface.
[0071] Example 16
[0072] Compared with Example 1, Example 16 is different in that the components of the suspending agent in the dry granular glaze are different, that is, the content of the water-soluble biopolysaccharide in the suspending agent of Example 16 is the lower limit: 5 parts. It is used to examine the suspension effect of the dry granular glaze and the concave-convex effect of the glaze surface.
[0073] Embodiment 17
[0074] Compared with Example 1, Example 17 is different in that the components of the suspending agent in the dry granular glaze are different, that is, the content of the water-soluble biopolysaccharide in the suspending agent of Example 17 is the upper limit: 10 parts. It is used to examine the suspension effect of the dry granular glaze and the concave-convex effect of the glaze surface.
[0075] Comparative Example 1
[0076] Compared with Example 1, the difference is that: Al in the dry particles 2 O 3 The content of is lower than the lower limit, and the chemical composition of the dry particles is as follows: Al 2 O 3 : 15.25%, SiO 2 : 65.73%, B 2 O 3 : 3.90%, K 2 O: 1.98%, Na 2 O: 2.05%, CaO: 3.34%, BaO: 3.88%, SrO: 2.92%, the rest are trace impurities and may be reduced as appropriate.
[0077] Comparative Example 2
[0078] Compared with Example 1, the difference is that: Al in the dry particles 2 O 3 The content of Al is higher than the upper limit, and the chemical composition of the dry particles is as follows: 2 O 3 : 22.10%, SiO 2 : 56.77%, B 2 O 3 : 5.80%, K 2 O: 1.86%, Na 2 O: 2.04%, CaO: 3.39%, BaO: 3.83%, SrO: 2.97%, the rest are trace impurities and may be reduced as appropriate.
[0079] Comparative Example 3
[0080] Compared with Example 1, the difference is that the content of waste glass in the dry granular raw material is 4 parts, which is lower than the lower limit. The chemical composition of the dry granules is specifically: Al 2 O 3 : 20.15%, SiO 2: 55.71%, B 2 O 3 : 5.56%, K 2 O: 1.87%, Na 2 O: 2.55%, CaO: 3.39%, BaO: 4.31%, SrO: 3.94%, the rest are trace impurities and can be reduced as appropriate.
[0081] Comparative Example 4
[0082] Compared with Example 1, the difference is that the content of waste glass in the dry granular raw material is 9 parts, which is higher than the upper limit. The chemical composition of the dry granules is specifically: Al 2 O 3 : 20.15%, SiO 2 : 64.17%, B 2 O 3 : 5.57%, K 2 O: 1.97%, Na 2 O: 2.65%, CaO: 3.41%, BaO: 4.32%, SrO: 3.14%, the rest are trace impurities and can be reduced as appropriate.
[0083] Comparative Example 5
[0084] Compared with Example 1, the difference is that the contents of BaO and SrO in the dry granule glaze are both lower than the lower limit, and the chemical composition of the dry granules is specifically: Al 2 O 3 : 19.13%, SiO 2 : 64.24%, B 2 O 3 : 4.97%, K 2 O: 2.17%, Na 2 O: 1.85%, CaO: 3.48%, BaO: 1.80%, SrO: 1.07%, the rest are trace impurities and may be reduced as appropriate.
[0085] Comparative Example 6
[0086] Compared with Example 1, the difference is that the contents of BaO and SrO in the dry granular glaze are both higher than the upper limit, and Al 2 O 3 : 18.55%, SiO 2 : 60.27%, B 2 O 3 : 4.67%, K 2 O: 1.77%, Na 2 O: 1.89%, CaO: 3.43%, BaO: 6.25%, SrO: 4.56%, the rest are trace impurities and can be reduced as appropriate.
[0087] Comparative Example 7
[0088] Compared with Example 1, the difference is that the Al in the matte inorganic glaze in the digital matte deep ink is 2 O 3 The content is lower than the lower limit, and its specific chemical composition is: Al 2 O 3 : 17.45%, SiO 2 : 50.36%, K 2 O: 3.27%, Na 2 O: 2.57%, CaO: 5.57%, ZnO: 5.45%, BaO: 9.46%, SrO: 7.37%, the rest are trace impurities and may be reduced as appropriate.
[0089] Comparative Example 8
[0090] Compared with Example 1, the difference is that the Al in the matte inorganic glaze in the digital matte deep ink is 2 O 3 The content is higher than the upper limit, and its specific chemical composition is: Al 2 O 3 : 22.54%, SiO 2 : 45.16%, K 2 O: 1.28%, Na 2 O: 1.89%, CaO: 4.17%, ZnO: 5.44%, BaO: 9.06%, SrO: 6.92%, and the rest are trace impurities and can be reduced as appropriate.
[0091] Comparative Example 9
[0092] Compared with Example 1, the difference is that the contents of divalent oxides ZnO, BaO, and SrO in the matte inorganic glaze in the digital matte engraving ink are all lower than the lower limit, and the specific chemical composition is: Al 2 O 3 : 21.55%, SiO 2 : 49.18%, K 2 O: 2.27%, Na 2 O: 1.44%, CaO: 4.57%, ZnO: 2.84%, BaO: 7.57%, SrO: 5.45%, the rest are trace impurities and may be reduced as appropriate.
[0093] Comparative Example 10
[0094] Compared with Example 1, the difference is that the contents of divalent oxides ZnO, BaO, and SrO in the matte inorganic glaze in the digital matte engraving ink are all higher than the upper limit, and the specific chemical composition is: Al 2 O 3 : 21.55%, SiO2 : 47.14%, K 2 O: 1.98%, Na 2 O: 2.39%, CaO: 4.96%, ZnO: 5.98%, BaO: 10.94%, SrO: 9.24%, the rest are trace impurities and can be reduced as appropriate.
[0095] Comparative Example 11
[0096] Compared with Example 1, the difference is that the composition of the suspending agent in the dry granular glaze is different, that is, the content of sodium polyacrylate in the suspending agent of Comparative Example 11 is lower than the lower limit, which is 3 parts.
[0097] Comparative Example 12
[0098] Compared with Example 1, the difference is that the composition of the suspending agent in the dry granular glaze is different, that is, the content of sodium polyacrylate in the suspending agent of Comparative Example 12 is higher than the upper limit, which is 12 parts.
[0099] Comparative Example 13
[0100] Compared with Example 1, the difference is that the composition of the suspending agent in the dry granular glaze is different, that is, the content of sodium alginate in the suspending agent of Comparative Example 13 is lower than the lower limit, which is 2 parts.
[0101] Comparative Example 14
[0102] Compared with Example 1, the difference is that the composition of the suspending agent in the dry granular glaze is different, that is, the content of sodium alginate in the suspending agent of Comparative Example 14 is higher than the upper limit, which is 10 parts.
[0103] Comparative Example 15
[0104] Compared with Example 1, the difference is that the composition of the suspending agent in the dry granular glaze is different, that is, the content of the water-soluble polysaccharide in the suspending agent of Comparative Example 15 is lower than the lower limit, which is 3 parts.
[0105] Comparative Example 16
[0106] Compared with Example 1, the difference is that the composition of the suspending agent in the dry granular glaze is different, that is, the content of the water-soluble polysaccharide in the suspending agent of Comparative Example 16 is higher than the upper limit, which is 12 parts.
[0107] Comparative Example 17
[0108] Compared with Example 1, the difference is that the dry granular glaze used in Comparative Example 17 is conventional dry granular, and its composition is: Al 2 O 3 : 15.24%, SiO 2 : 67.57%, K 2 O: 3.68%, Na 2O: 4.67%, CaO: 1.48%, MgO: 1.57%, B 2 O 3 : 4.65%, the rest is reduced and trace impurities.
[0109] Comparative Example 18
[0110] Compared with Example 1, the difference is that: Comparative Example 18 uses ordinary digital engraving ink, whose composition is: Al 2 O 3 : 21.24%, SiO 2 : 56.56%, K 2 O: 4.65%, Na 2 O: 5.77%, CaO: 2.88%, MgO: 2.97%, B 2 O 3 : 4.05%, the rest are trace impurities and discretionary reduction. Used to examine the influence of ordinary ink on the brightness of concave and convex texture position and the three-dimensional effect of texture.
[0111] Comparative Example 19
[0112] Compared with Example 1, the difference is that: Example 19 uses a common suspending agent, whose ingredients are: 5 parts of sodium methyl cellulose, 83 parts of ethylene glycol, 10 parts of glycerin and 2 parts of bentonite, as the main suspending agent for dry particles, to examine the effect of the common suspending agent on the formation of a concave and convex texture effect on the glaze surface.
[0113] Performance Testing
[0114] Glossiness of ceramic tile glaze: The specific glossiness of the glaze can be measured by a digital photometer.
[0115] Glaze acid and alkali resistance and anti-fouling performance: The test basis is GB / T4100-2015, "Ceramic Tiles" Appendix G Dry-pressed Ceramic Tiles (E≤0.5Bia class).
[0116] Glaze concave and convex texture effect: based on visual inspection of the layout effect.
[0117] Glossiness of concave and convex textures: The specific glossiness of the glaze can be measured by a digital photometer.
[0118] Pattern clarity: Mainly through visual inspection, observing texture details and pattern layering effects.
[0119] The results are shown in Table 1.
[0120]
[0121]
[0122]
[0123]
[0124]
[0125]
[0126] from Figure 1 and Figure 3 It can be seen from the appearance of the ceramic tiles that the ceramic tiles prepared by the present invention have a natural texture like natural marble, and the overall glaze surface presents a clearly visible concave-convex effect, and the concave-convex effect is three-dimensional and has rich texture. Figure 2 The optical microscope diagram shows that the glaze surface has micro cracks with a fineness of 50μm. Figure 1 As can be seen from the performance tests in the above table, the glaze is matte, with soft light, good transparency, acid and alkali resistance, dirt resistance, and excellent physical properties, which can ensure that the product has a wide range of applications.
[0127] In Comparative Example 1, due to the Al 2 O 3 The content is too low, causing the glaze surface of the tile to collapse after firing, and it is not three-dimensional enough. 2 O 3 The content is high, which makes the glaze surface of the tile rough after firing. Figure 4 It can be seen that the glaze pattern of the tile prepared in Comparative Example 2 is blurred and not clear enough. Figure 3 Compared with the pattern clarity of the ceramic tile obtained in Example 2, there is a significant difference.
[0128] In comparative example 3, due to the less use of waste glass, the glaze transparency is poor and the pattern is not clear enough. In comparative example 4, due to the more use of waste glass, the glaze collapses and is not three-dimensional enough.
[0129] In Comparative Example 5, due to the low content of divalent barium and strontium in the dry granular glaze, the glaze surface is not three-dimensional enough, there are more crystals, and the transparency of the glaze surface is poor. In Comparative Example 6, due to the high content of divalent barium and strontium in the dry granular glaze, the acid and alkali resistance of the tile is unqualified, the glaze layer is easy to react with acid, and the transparency of the glaze surface is poor.
[0130] In Comparative Example 7, due to the Al 2 O 3 The content of Al in the digital matte engraving ink is too low, resulting in a bright gloss at the concave and convex positions formed after the reaction with the dry granular glaze, and the texture is poor. 2 O 3The content of is too high, resulting in the glossiness and dryness of the concave and convex positions formed after the reaction with the dry granular glaze.
[0131] In Comparative Example 9, due to the low content of divalent oxides of zinc, barium, and strontium in the digital matte engraving ink, the glaze surface collapsed at the concave and convex positions, and the glossiness was bright. In Comparative Example 10, due to the excessive content of divalent oxides of zinc, barium, and strontium in the digital matte engraving ink, the glaze surface was too matte at the concave and convex positions due to the reaction with the dry granular glaze, resulting in dryness, dullness, and no texture at the concave and convex positions.
[0132] In Comparative Example 11, due to the small amount of sodium polyacrylate used in the suspending agent of the dry granule glaze, the adsorption force of the suspending agent on the dry granules is insufficient, making it difficult to form a fine dispersing effect. In Comparative Example 12, due to the excessive amount of sodium polyacrylate used in the suspending agent, the suspending agent has high viscosity and is difficult to form a dispersing effect.
[0133] In Comparative Example 13, since the amount of sodium alginate in the suspending agent is small, the hydrophilic property of the suspending agent is small, and it is difficult to form a displacing effect. In Comparative Example 14, since the amount of sodium alginate in the suspending agent is large, the viscosity of the suspending agent is too large. When the suspending agent with too large viscosity encounters digital matte deep ink, it is difficult to form a fine displacing effect.
[0134] In Comparative Example 15, due to the small amount of water-soluble polysaccharide in the suspension formula, the electrolyte in the dry granular glaze is small, and it is difficult to form a repelling effect when the suspension meets the digital matte engraving ink. In Comparative Example 16, due to the large amount of water-soluble polysaccharide in the suspension formula, the viscosity of the suspension increases. When it meets the digital matte engraving ink, the repulsive force formed is difficult to form a good repulsion of the dry granular glaze, so it is difficult to form a relatively fine, concave and convex texture effect.
[0135] In Comparative Example 17, conventional dry particles were selected. Since the formula did not match this process, the glaze surface collapsed and the texture pattern was unclear.
[0136] In Comparative Example 18, conventional digital engraving ink is used instead of the digital matte engraving ink of the present invention. Due to the lack of barium strontium components in the conventional digital engraving ink, the glossiness at the concave and convex positions is brighter, the natural effect is poor, and the effect at the concave and convex positions collapses.
[0137] In Comparative Example 19, conventional suspending agents are used as the suspension medium of dry granular glaze. Since conventional dry granular glaze contains a large amount of organic components, it is difficult to form a mutually repulsive force when it encounters digital matte engraving ink, making it difficult to form a fine concave-convex effect.
[0138] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A ceramic tile with a velvet texture and a replica of an original stone, characterized in that: It includes a body layer, a surface glaze layer, a pattern texture layer, a digital engraving ink layer, and a dry granular glaze layer arranged in sequence from bottom to top; the digital engraving ink layer is composed of digital matte engraving ink; the dry granular glaze layer is composed of dry granular glaze; a surface tension difference is formed between the digital matte engraving ink and the dry granular glaze; Calculated by weight, the digital matte engraving ink includes 60-65 parts of organic solvent and 35-40 parts of matte inorganic glaze; the chemical composition of the matte inorganic glaze is: Al2O3: 18.45%-21.54%, SiO2: 45.68%-50.24%, K2O: 1.24%-3.25%, Na2O: 1.25%-2.58%, CaO: 4.37%-6.58%, ZnO: 3.24%-5.58%, BaO: 8.57%-10.24%, SrO: 6.35%-8.54%, and the rest are trace impurities and are reduced as appropriate; Calculated by weight, the dry granule glaze comprises 30-40 parts of dry granules and 60-70 parts of suspending agent; the chemical composition of the dry granules is: Al2O3: 16.21%-20.14%, SiO2: 58.12%-63.34%, B2O3: 4.27%-7.54%, K2O: 1.34%-2.34%, Na2O: 1.56%-2.54%, CaO: 2.14%-4.57%, BaO: 2.10%-5.65%, SrO: 1.87%-3.98%, and the rest are trace impurities and reduced as appropriate; The suspending agent comprises the following components: 1.5 to 3.5 parts of sodium methylcellulose, 5 to 10 parts of sodium polyacrylate, 3 to 8 parts of sodium alginate, 5 to 10 parts of water-soluble biopolysaccharide and 70 to 85 parts of water.
2. The ceramic tile with a velvet texture and a replica of an original stone according to claim 1, characterized in that: The surface tension of the digital matte deep ink is 1.25×10 -2 N / m~2.27×10 -2 N / m, the surface tension of the dry granular glaze is 6.50×10 -2 N / m~6.80×10 -2 N / m.
3. The ceramic tile with a velvet texture and a replica of an original stone according to claim 1, characterized in that: Calculated by mass percentage, the organic solvent includes the following components: Isooctyl laurate 40%-55%, ethyl acetate 40%-55%, dispersant 3%-6%, suspending agent 0.1%-0.2%, defoaming agent 0.2%-0.3%, leveling agent 0.3%-0.6%, pH adjuster 0.15%-0.3%.
4. The ceramic tile with a velvet texture and a replica of an original stone according to claim 1, characterized in that: The raw materials of the dry particles are: calcined kaolin: 18-22 parts, potassium feldspar: 15-25 parts, sodium feldspar: 18-28 parts, waste glass: 5-8 parts, corundum: 3-6 parts, sodium borate: 8-12 parts, fluorite: 3-7 parts, barium carbonate: 3-7 parts, and strontium sulfate: 4-8 parts.
5. The ceramic tile with a velvet texture and a replica of an original stone according to claim 4, characterized in that: The raw materials constituting the dry particles are calcined and melted to form a frit, and then the frit is ground and the suspending agent is added to form the dry particle glaze with a particle size ranging from 80 to 120 μm.
6. A method for preparing a ceramic tile having a velvet texture and a replica of an original stone, characterized in that: Follow these steps: S1, pressing the powder to form a green body layer; S2, applying a glaze on the body layer to form a glaze layer; S3, firstly printing color texture on the surface glaze layer to form a pattern texture layer; then printing digital glaze matte deep ink on the pattern texture layer to form a digital deep ink layer; S4, applying dry granular glaze on the formed digital deep ink layer to form a dry granular glaze layer; S5. The green body layer coated with the dry granular glaze is fired and formed to obtain a ceramic tile having a velvet texture and a replica of the original stone effect as described in any one of claims 1 to 5.
7. The method for preparing a ceramic tile having a velvet texture and a replica of an original stone according to claim 6, characterized in that: The powder in step S1 is pressed into a brick by a brick press and dried. After drying, the moisture content of the brick is controlled below 0.5%, and the strength of the brick is controlled above 1.8 MPa.
8. The method for preparing a ceramic tile having a velvet texture and a replica of an original stone according to claim 6, characterized in that: The chemical composition of the glaze in step S2 is: Al2O3: 23.24% to 25.67%, SiO2: 51.24% to 53.65%, ZrO2: 6.32% to 8.58%, K2O: 2.45% to 3.68%, Na2O: 1.67% to 2.69%, CaO: 1.17% to 2.56%, MgO: 2.30% to 3.65%, Fe2O3: 0.56% to 0.89%, TiO2: 0.35% to 0.68%, and the rest are reduced as appropriate.
9. The method for preparing a ceramic tile having a golden velvet texture and a replica of an original stone according to claim 8, characterized in that: The specific gravity of the glaze is 1.85-1.90 g / ml, and the glaze application amount is 300-400 g / m 2 .
10. The method for preparing a ceramic tile having a golden velvet texture and a replica of an original stone according to claim 6, characterized in that: The firing temperature of the sintering molding in the step S5 is 1180-1190° C., and the firing time is 60-65 minutes.
Citation Information
Patent Citations
Stereo-positioning effect dry granule complete-polished ceramic brick and preparation method thereof
CN110396005A
Starlight dry granules and preparation method thereof, glazed ceramic tile with starlight effect and preparation method and application of glazed ceramic tile
CN114853343A
Golden velvet glaze, golden velvet ceramic rock plate and preparation method of golden velvet ceramic rock plate
CN117923799A
Colorful marble tile with 3D digital mold effect and preparation method of colorful marble tile
CN118145975A
Dry granule ceramic tile from wet-method slurry spraying processing and preparation method therefor
WO2020233032A1
Cited By
Raw stone embossed rock plate and production process thereof
CN120554149A
A kind of raw stone relief rock plate and its production process
CN120554149B
Hydrophobic matte archaized brick and preparation method thereof
CN120887737A
Hydrophobic matte antique brick and method for preparing the same
CN120887737B
